Condition of perceived self-efficacy as a predictive of student readiness in college tasks - Yuzarion Yuzarion; Alfaiz Alfaiz; Rici Kardo; Lovelly Dwinda Dahen (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2017)
Self-efficacy is the psychological aspect that shapes human activity. It comes from experience and ability about themselves to accomplish the task. In this article, discussed research findings in 2012 and 2015 on self-efficacy perception students in readiness to complete the task of college, whether there is a change during the period from three years after the condition of efficacy himself in completing the task. This research used a quantitative descriptive method, and took with proportional stratified random sampling. Research in 2012 found that perceptions of self-efficacy students in completing a lecture in the level of underprivileged and research in 2015 found that the level capable and have a contribution in preparedness in completion of the task. The question that will be discussed throughout this article, does self-efficacy have the effect of different educational backgrounds? These findings have an impact of the reality in the practice of counseling services which researchers and colleagues must recognize and handle.